Using Qualitative Data Analysis Software to Support Digital Research Workflows. (March 2023) - Paulus, Trena M.
While software packages such as NVivo are typically considered useful for qualitative data analysis, in actuality they are powerful and flexible enough to serve as the central component of a robust digital research workflow. Various features of these packages can be used across the entire research process from reviewing the literature to writing up the study's findings. This article provides an overview of available qualitative data analysis software (QDAS) packages, including how to: use software tactics to enact research design strategies; select an appropriate QDAS package; report the use of software in the research report; and consider implications of QDAS use for human resource development scholars.